Ding-Zhi-Xiao-Wan decoction alleviates mitochondrial autophagy in vascular dementia mice via the PI3K/Akt/mTOR pathway - Minzhen Deng; Xiaoqin Zhong; Zhenqiu Ning; Yu Wang; Dafeng Hu; Han Zhang; Liping Huang (Phytomedicine Plus, 2024)
Background: Vascular dementia (VD) is a common and diverse group of neurological disorders. The cause of cognitive impairment symptoms in VD is mainly cerebrovascular lesions caused by various factors. Ding-Zhi-Xiao-Wan decoction (DZXW) is a classical Chinese medicine compound for treating clinical manifestations of dementia-like conditions. Our preliminary study determined that the volatile oil component (β-asarone) of Acorus tatarinowii Schott in DZXW has a significant neuroprotective effect. However, there is limited documentation on the effects of DZXW in treating VD. Methods: The analysis of medicinal chemistry, potential targets, and mechanisms of DZXW for treating VD started with network pharmacology. To create the VD model, bilateral carotid artery ligation was performed. Normal saline or DZXW was administered to Institute of Cancer Research mice via gavage daily for 28 days. The Morris water maze test was used to evaluate the learning and memory abilities of the mice post-treatment. To validate potential targets and efficacy mechanisms identified through network pharmacology, qualitative real-time PCR and western blotting were employed. Further examination of histopathological and ultrastructural changes in the hippocampal region was conducted using hematoxylin-eosin and Nissl staining, immunofluorescence, and transmission electron microscopy. Results: The analysis using network pharmacology showed that there was a connection between the key targets associated with the components of DZXW, there were 836 targets of ginseng, 305 targets of Acorus tatarinowii Schott, 394 targets of Poria cocos, and 228 targets of Polygala tenuifolia; and 4671 targets related to VD. In particular, 53 targets are at the intersection of DZXW and VD. The results of this experiment confirmed that DZXW not only attenuated brain damage and its induced learning memory deficits in the VD model but also had some antioxidant effects. Furthermore, DZXW down-regulated VD-induced CASP3, EGFR, PTGS2, ESR1, and HSP90AA1 mRNA expression. It was confirmed that DZXW enhanced the phosphorylation of PI3K, Akt, and mTOR. Additionally, DZXW was demonstrated to elevate the protein levels of p62 and TOM20 while reducing the protein expression of mitochondrial autophagy markers such as PINK1, PARKIN, Beclin-1, and LC3. Conclusions: DZXW impedes mitochondrial autophagy through the activation of the PI3K/Akt/mTOR signaling pathway. This leads to the reduction of mitochondrial injury in nerve cells triggered by VD-induced tissue hypoglycemia and hypoxia, ultimately enhancing cognitive function and memory retention.